CLASSICAL LAMINATES THEORY: APPLICATION TO COMBINED COMPOSITE CFRP/GFRP - Md Zahir, N.A.A.; Daud, M.A.M.; Ab Ghani, A.F.; Alami, F. (Journal of Advanced Manufacturing Technology (JAMT), 2020)
The advantages of using hybrid composite in terms of mechanical properties and flexibility of choosing materials made them extensively used in high precision industries. However, the study involving hybrid composite for optimized design is complicated and involves complex mathematical computation. In order to unlock the full potential of hybrid composite, the number of parameters which influence the modulus of elasticity of hybrid composite such as lay-up sequence, configurations and thickness layup is studied for the purpose of design optimization for hybrid composite CFRP/GFRP laminates. In this research, Glass Fiber Reinforced Polymer (GFRP) ply is added into high modulus of Carbon Fiber Reinforced Polymer (CFRP). The method utilized in this research is analytical approach via MATLAB R2012b along with validation by using eLamX2 composite laminates software. The outcomes of this study indicate that the higher number of CFRP plies in the hybrid composite laminates will increase the modulus of elasticity of the laminates. The position of CFRP ply at the outermost of hybrid composite laminates increased the bending stiffness of overall laminates. For CFRP reduced thickness, the extensional stiffness decreases when compared to baseline and third method. Thinner GFRP layup may increase the modulus of elasticity of composite laminates.